Effectiveness of mid-regional pro-adrenomedullin, compared to other biomarkers (including lymphocyte subpopulations and immunoglobulins), as a prognostic biomarker in COVID-19 critically ill patients: New evidence from a 15-month observational prospective study - Montrucchio, Giorgia; Sales, Gabriele; Balzani, Eleonora; Lombardo, Davide; Giaccone, Alice; Cantù, Giulia; D'Antonio, Giulia; Rumbolo, Francesca; Corcione, Silvia; Simonetti, Umberto; Bonetto, Chiara; Zanierato, Marinella; et al. (Frontiers in Medicine, 2023)
Background Mid-regional Pro-Adrenomedullin (MR-proADM), an endothelium-related peptide, predictive of death and multi-organ failure in respiratory infections and sepsis, seems to be effective in identifying COVID-19 severe forms. The aim of the study is to evaluate the effectiveness of MR-proADM, in comparison to routine inflammatory biomarkers, lymphocyte subpopulations, and immunoglobulin (Ig) at Intensive Care Unit (ICU) admission and over time, in predicting mortality in severe COVID-19 patients. Methods All adult COVID-19 pneumonia patients admitted between March 2020 and June 2021 in the ICUs of a university hospital in Italy were enrolled. MR-proADM, lymphocyte subpopulations, Ig and routine laboratory test were measured within 48 hours and on day 3 and 7. Survival curves, with MR-proADM cut-off >1.5 nmol/L, were compared using the Log-rank test. Predictive ability was compared using area under the curve (AUC) and 95% confidence interval (CI) of different receiver-operating characteristics curves. Results 209 patients, with high clinical severity (SOFA 7, IQR 4-9; SAPS II 52, IQR 41-59; Median Viral Pneumonia Mortality Score – MuLBSTA - 11, IQR 9-13) were enrolled. ICU and overall mortality were 55.5% and 60.8%, respectively. Procalcitonin, lactate dehydrogenase, D-dimer, N-terminal prohormone of brain natriuretic peptide, myoglobin, troponin, neutrophile count, lymphocyte count, and natural killer lymphocyte count were significantly different between survivors and non-survivors, while lymphocyte subpopulations, and Ig were not different in the two groups. MR-proADM was significantly higher in non-survivors (1.17±0.73 vs 2.31±2.63, p<0.0001). A value >1.5 nmol/L was an independent risk factor for mortality at day-28 (odds ratio of 1.9 [IC 95%: 1.220-3.060]) after adjusting for age, lactate at admission, SOFA, MuLBSTA, superinfections, cardiovascular disease and respiratory disease. The MR-proADM trends evaluated within 48 hours of admission, on days 3 and 7 of ICU stay, maintained a correlation with mortality (p<0.0001). Compared to all other biomarkers considered, MR-proADM value within 48 hours had the best accuracy in predicting mortality at day-28 (AUC=0.695 [ CI95%: 0.624-0.759]). Conclusions MR-proADM seems to be the best biomarker for mortality risk stratification in severe COVID-19-patient. Ig levels and lymphocyte subpopulations (except for natural killers) seem not correlated with mortality. Larger, multicentric studies are needed to confirm these findings.